Evolutionary studies of wheat streak mosaic-associated viruses and characterization of the wheat virome - Redila, Carla Bianca Dizon (Kansas State University, 2021)
Wheat viruses including Wheat streak mosaic virus (WSMV), Triticum mosaic virus (TriMV), High Plains wheat mosaic emaravirus (HPWMoV), and Barley yellow dwarf virus (BYDV) cost substantial losses in crop yields annually. Although there have been extensive studies conducted on known wheat viruses, currently, there is limited knowledge about all viral components associated with wheat (Triticum aestivum L.) including potential novel viruses. Wheat streak mosaic (WSM), a disease of cereals and grasses, costs Kansas farmers millions in yield losses. Although WSMV is considered as the main causal agent of WSM, TriMV and HPWMoV have also been reported in mixed infections. While resistant varieties are utilized to minimize the effects of the disease, genetic variation in associated viruses increases the emergence of potential resistance-breaking isolates. Currently, little is known about the genetic composition of populations of WSM-associated viruses in the field. This study first aims to analyze the genetic variation and characterize the evolutionary mechanism(s) applied by WSM-associated viruses in the field using complete genomes sequences, and also to determine and characterize all viral populations associated with wheat. Field collections of 24 WSM-like symptomatic and asymptomatic wheat samples were used for total RNA deep sequencing, along with 5 historic WSMV samples for the evolutionary studies. Through bioinformatics analysis, sequences were mapped to available reference genomes and de novo assembled to identify new viruses. Results of the 2019 field survey showed WSMV as the predominant virus followed by mixed infections of WSMV+TriMV. Recombination was observed to be a major evolutionary force for WSMV but not for TriMV isolates. Phylogenetic analyses based on the obtained full genome sequences demonstrated that, unlike other isolates from the United States, Kansas isolates are widely distributed in sub-clades. Moreover, the phylogenetic studies suggested that TriMV field isolates may be under selection pressure to introduce genetic variations due to the use of resistant varieties in the fields. The full genome sequence of a new Kansas HPWMoV isolate was reported here. In addition to known wheat viruses, viral sequences sharing significantly low (<40%) similarity with potyviruses and recently discovered virga-like viruses were identified. Our analysis showed that these viral sequences belong to a novel putative virus tentatively named Wheat-associated vipovirus (WaVPV). Additionally, fungal-associated viruses, such as Mitovirus, were also identified. The findings of this study provide a better understanding of the current status of the genetic structure of WSM-associated viruses in Kansas fields. This, in turn, can aid in developing efficient and durable disease control strategies. The discovery and characterization of novel viruses potentially associated with wheat is important to determine if they may pose a threat to the wheat industry or have the potential to be used as new biological control agents for wheat pathogens.
Keywords: Wheat virome; Virus evolution; RNA sequencing; Wheat streak mosaic disease; Virus discovery